‘De scharpheit van een gladde tong’. Literaire teksten en publieke opinievorming in de vroegmoderne Nederlanden - Jan Bloemendal; Arjan van Dixhoorn (BMGN: Low Countries Historical Review, 2010)
‘The Sharpness of a Smooth Tongue’. Literary Texts and the Formation of Public Opinion in the Early Modern Netherlands The Low Countries hardly play any role in international debates about the history of the formation of public opinion in early modern Europe. In the wake of Jürgen Habermas, historians have focused in particular on late seventeenthand eighteenth-century England and France. Scholars have criticised the notion that it was during the eighteenth century that the formation of free public opinion came into existence due to a combination of the periodical press, its critical role and a national readership. Nevertheless, the period before 1700 is hardly referred to at all during discussions about the role of public opinion. During that time a permanent, structured public openness did not exist. However, in the early modern Low Countries many socio-cultural and institutional conditions seem to be present which made the formation of critical public opinion among the population possible. The literary culture of these regions offers an important research subject for studies into the formation of public opinion.